2009
DOI: 10.1590/s1679-62252009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ca2+-management between the ventricle of two species of neotropical teleosts: the jeju, Hoplerythrinus unitaeniatus (Spix & Agassiz, 1829), and the acara, Geophagus brasiliensis (Quoy & Gaimard, 1824)

Abstract: This study analyzed the physiological role of the cardiac sarcoplasmic reticulum (SR) of two neotropical teleosts, the jeju, Hoplerythrinus unitaeniatus (Erythrinidae), and the acara, Geophagus brasiliensis (Cichlidae). While the in vivo heart frequency (f H -bpm) of acara (79.6 ± 6.6) was higher than that of the jeju (50.3 ± 2.7), the opposite was observed for the ventricular inotropism (Fc -mN/mm 2 ) at 12 bpm (acara = 28.66 ± 1.86 vs. jeju = 36.09 ± 1.67). A 5 min diastolic pause resulted in a strong potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A number of in vivo and in vitro studies have examined the effects of temperature and oxygen deprivation on the cardiovascular status and cardiac physiology of air-breathing fishes (Costa et al 2005; Costa et al 2009; Iversen et al 2013; McKenzie et al 2007), but none have investigated cardiac excitation-contraction coupling at the level of the isolated cardiomyocyte. Our measurements of cardiomyocyte morphology revealed that ventricular cardiomyocytes of Alaska blackfish are long and thin, much like those of other non-mammalian species (Galli et al 2006; Galli et al 2009; Vornanen et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vivo and in vitro studies have examined the effects of temperature and oxygen deprivation on the cardiovascular status and cardiac physiology of air-breathing fishes (Costa et al 2005; Costa et al 2009; Iversen et al 2013; McKenzie et al 2007), but none have investigated cardiac excitation-contraction coupling at the level of the isolated cardiomyocyte. Our measurements of cardiomyocyte morphology revealed that ventricular cardiomyocytes of Alaska blackfish are long and thin, much like those of other non-mammalian species (Galli et al 2006; Galli et al 2009; Vornanen et al 2002).…”
Section: Discussionmentioning
confidence: 99%